Network Implementation Analysis on Democratic Public Service - Azis, Alwi (BISNIS & BIROKRASI: Jurnal Ilmu Administrasi dan Organisasi, 2013)
This research aims at describing the implementation of a democratic public service (public transportation) among organizational networks in Makassar City. The researcher used a qualitative method and a study case strategy. Data gathering was done through observation, intensive interviews, and document analysis. A case study analysis was used for processing the data and a technical analysis description. Results of this research reveal that the implementation of an inter-organizational network public service (public transportation) is not yet effective. This can be seen from: 1) Regulations: the Makassar City Traiffic and Public Transportation Forum, as an outlet for stakeholders of public transportation, has not been socialized in an effective manner; 2) Commitment: implementors in the field have not shown any commitment to the program; 3) Source: implementors do not share resources; 4) Cooperation: there is no cooperation with other insitutions to support the implementation of the program that has been laid down by the Traffic and Public Transportation Forum; 5) Coordination: each implementor runs the program according to their main duties and functions from their respective institutions; 6) Collaboration: The Forum has not collaborated with other parties in implementing the program; 7) Participation: not all stakeholders or participants are involved in the Forum’s programs.